Предмет: Алгебра,
автор: Monzaemon
Ответы
Автор ответа:
0
x⁸-6x⁴=7
(x⁴)²-6*(x⁴)-7=0
замена переменных: x⁴=t, t≥0
t²-6t-7=0
D=(-6)²-4*1*(-7)=36+28=64
t₁=-1. -1<0 посторонний корень
t₂=7
обратная замена:
t=7, x⁴=7
x²=+-√7. x²≠-√7
x²=√7,
x₁=-⁴√7, x₂=⁴√7
(x⁴)²-6*(x⁴)-7=0
замена переменных: x⁴=t, t≥0
t²-6t-7=0
D=(-6)²-4*1*(-7)=36+28=64
t₁=-1. -1<0 посторонний корень
t₂=7
обратная замена:
t=7, x⁴=7
x²=+-√7. x²≠-√7
x²=√7,
x₁=-⁴√7, x₂=⁴√7
Похожие вопросы
Предмет: Физика,
автор: Snejanavalikova
Предмет: Алгебра,
автор: rotarvladislav3
Предмет: Английский язык,
автор: nosirtv
Предмет: Биология,
автор: ValerianLavandovich